2012
DOI: 10.1021/om200641u
|View full text |Cite
|
Sign up to set email alerts
|

Indenyl Functionalized N-Heterocyclic Carbene Complexes of Chromium: Syntheses, Structures, and Reactivity Studies Relevant to Ethylene Oligomerization and Polymerization

Abstract: The chromium(III) complexes of the type L1CrXY (L1 = 1-(2,6-diisopropylphenyl)-3-[β-(4,7-dimethylindenyl)ethyl]-imidazol-2-ylidene, X, Y = Cl, 2a-Cl; X = Cl, Y = Me, 2a-Me; X = Cl, Y = Ph, 2a-Ph; X, Y = benzyl, 2a-Bz) and L2CrCl2 (L2 = 1-(2,6-diisopropylphenyl)-3-[γ-(4,7-dimethylindenyl)propyl]-imidazol-2-ylidene, 2b-Cl) have been prepared and characterized by analytical and diffraction methods. The salts [L1CrCl(THF)]+[BArF 4]− and [L2CrCl(THF)]+[BArF 4]− (ArF = 3,5-bis(trifluoromethyl)phenyl) were also chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The solid was soluble in THF, and layering pentane onto the THF solution yielded single crystals of which structure was elucidated to be MeCrCl 2 (THF) 3 via X-ray crystallographic studies. 42,43…”
Section: Reaction Of (Eh) 2 Croh With Aluminum Compoundsmentioning
confidence: 99%
“…The solid was soluble in THF, and layering pentane onto the THF solution yielded single crystals of which structure was elucidated to be MeCrCl 2 (THF) 3 via X-ray crystallographic studies. 42,43…”
Section: Reaction Of (Eh) 2 Croh With Aluminum Compoundsmentioning
confidence: 99%
“…CpCr(III)-NHC complexes[169] 4.1.1.3 Indenyl functionalized NHC complexes of CrIn 2012,Danopoulos and Hanton et al[170] reported the synthesis of indenyl functionalized NHC complexes of Cr(II). Complex Cr-51 (Figure 4.5) was synthesized from the reaction of CrCl 2 with the potassium salt of the indenyl functionalized ligand[170].…”
mentioning
confidence: 99%
“…Complex Cr-51 (Figure 4.5) was synthesized from the reaction of CrCl 2 with the potassium salt of the indenyl functionalized ligand[170]. It adopts a distorted three coordinate geometry with Cr-C carbene distance of 2.075(4) Å.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 During the last few years, our research group in collaboration with Peris and co-workers has developed a new class of bidentate cyclopentadienyl ligands tethered to N-heterocyclic carbenes (NHCs) (A, Scheme 1). [4][5][6][7][8][9][10][11][12] Related indenyl-functionalised NHCs have been described by Danopoulos, [13][14][15][16] Wang 17 and others. 18 An important feature of these Cp-NHC chelating ligands is the possibility of independently varying their structural components, namely the cyclopentadienyl ring, the spacer, and the imidazolium ring in order to fine tune the steric and electronic properties of the ligand.…”
Section: Introductionmentioning
confidence: 99%